Comparison of the Effectiveness of Quizizz and Quizlet in Evaluating Social Studies Learning in Junior High Schools - Majid, Zinadine Zidan; Setyaditama, Muhammad Brilian; Wahyunengsih, Wahyunengsih (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study explores the comparative effectiveness of Quizizz and Quizlet in evaluating social studies learning among junior high school students. Using responses from four educators who assessed both platforms across 15 indicators each, the results reveal that both tools are highly effective in enhancing the learning process. Quizizz slightly outperformed Quizlet in average score, suggesting a marginal preference likely influenced by its interactive design and real-time feedback. Meanwhile, Quizlet showed strong utility in supporting independent learning through its flashcard-based format. Despite the small sample size, the findings indicate that both digital platforms are well-suited to support classroom assessment strategies and foster student engagement. The close performance of both tools highlights their complementary value, providing educators with flexible options to enhance the assessment experience. Further exploration is encouraged to validate these outcomes across broader contexts.